Assessment of fungal contamination in dangke, a traditional cheese product from small-scale producers in Enrekang, South Sulawesi - SETIAWAN PUTRA SYAH; MIRNAWATI B. SUDARWANTO; IDWAN SUDIRMAN; ANDI NURUL MUKHLISAH; WENY DWI NINGTYAS; MUHAMMAD IRFAN (Society for Indonesian Biodiversity, 2025)
Abstract. Syah SP, Sudarwanto MB, Sudirman I, Mukhlisah AN, Ningtyas WD, Irfan M. 2025. Assessment of fungal contamination in dangke, a traditional cheese product from small-scale producers in Enrekang, South Sulawesi. Biodiversitas 26: 3324-3333. Dangke is a traditional soft cheese produced in Enrekang, South Sulawesi, Indonesia, using household-scale methods that can pose significant food safety risks due to inadequate hygiene practices. This study assessed the level and diversity of fungal contamination in dangke collected from small-scale producers across Enrekang Regency. A total of 20 samples were collected aseptically and analyzed using the Total Plate Count (TPC) method on Sabouraud Dextrose Agar. The results showed that the average fungal count was 5.2 × 10? CFU/g, which greatly exceeded the maximum acceptable limit for solid dairy products (10 CFU/g) according to Codex Alimentarius guidelines. Phenotypic identification revealed the presence of both yeasts (75%) and molds (25%), with nine fungal genera detected. Candida sp. was the dominant genus (30%), followed by Saccharomyces sp. (16%), Geotrichum sp. (11%), Microsporum sp. (13%), Cladosporium sp. (9%), Penicillium sp. (9%), Aspergillus sp. (6%), Rodotorula sp. (5%), and Fusarium sp. (2%). Several of these genera, such as Aspergillus and Fusarium, are known producers of mycotoxins that pose potential health risks. These findings highlight the urgent need for improved hygiene practices, proper handling, and better storage conditions in traditional dangke production to reduce fungal contamination and ensure product safety for consumers.